Occupational zoonoses in zoo and wildlife veterinarians in India: A review - H. B. Chethan Kumar (Veterinary World, 2013)
Zoos and biological parks are considered as a hub for public ecreation and education. This is highlighted by the fact that visitors to the zoos are increasing year by year and they generate sizeable revenue. Veterinary professionals play a pivotal role in health management of wild animals in zoos and biological parks. Since veterinarians work in close contact with wild animals, there is a potential risk of transmission of zoonotic diseases from wild animals to humans and vice versa. There are approximately 1415 infectious agents causing diseases in humans, out of which 868 (61%) are known to be zoonotic in nature. It is also important to note that more than 70% of the emerging zoonotic diseases have wild animals as reservoir hosts. The major zoonotic diseases that are transmitted from wild animals to humans include rabies, anthrax, leptospirosis, Q-fever, psittacosis, hendra virus, nipah virus, herpes B encephalitis, toxoplasmosis, etc. Hence, it is imperative for veterinarians and zoo staff to be fully aware of the knowledge pertaining to the source, transmission, pathogenicity, treatment and control of zoonotic diseases. In this manuscript, we provide key information regarding zoonotic diseases and also recommend important measures for their control and prevention. The information provided here will be highly beneficial for personnel who work in close association with wild animals